How Supply Chain Transparency Boosts Business Value - Kraft, Tim; Zheng, Yanchong (MIT Sloan Management Review, 2021)
Companies face heightened scrutiny of how their products are made, including their suppliers' labor practices and environmental impacts. Across a range of industries, including apparel and consumer electronics, companies are facing pressures from all sides to demonstrate better environmental and social practices in their supply chains. This article explains how companies stand to benefit from increasing visibility into their supply chains and provides recommendations for doing so.